Tafsir Sunda: Urgensi Pelestarian Budaya Lokal - Muhammad Ihsan (UIN Siber Syekh Nurjati Cirebon, 2025)
This article aims to analyze the urgency of preserving Sundanese Quranic exegesis amidst the social changes brought about by digitalization, globalization, and modernization. For years, Sundanese exegesis has played a central role in imparting religious teachings to the people of West Java. This central role is inseparable from the contributions of the mufassir (exegete) who compiled it. Most Sundanese exegeses were written by kyai and ajengan from pesantren (Islamic boarding schools), who hold a distinguished position within the community. Kyai and ajengan are recognized for their ability to influence the character, behavior, and worldview of their society. However, the significant role of Sundanese exegesis has gradually diminished due to social changes, which alter paradigms, perspectives, and even religious practices. This study employs a literature review method with descriptive analysis to explore the urgency of Sundanese exegesis in light of these ongoing social changes. The findings of this study demonstrate that Sundanese exegesis plays a crucial role in preserving local culture through the use of Sundanese linguistic registers, proverbs, and expressions of Sundanese natural imagery, which are not found in other exegeses.